1996
DOI: 10.1093/ajcp/106.6.776
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between MIB-1 Staining Index and the Immunoreactivity of p53 Protein in Recurrent and Non-recurrent Meningiomas

Abstract: C o r r e l a t i o n B e t w e e n M I B -1 S t a i n i n g I n d e x a n d t h e I m m u n o r e a c t i v i t y o f p 5 3 P r o t e i n i nR e c u r r e n t a n d N o n -r e c u r r e n t M e n i n g i o m a s Wild type p53 protein has been shown by recent investigations to be involved in the negative regulation of cell proliferation, whereas aberrant p53 protein has lost this negative regulation of cell growth. Wild type pS3 protein, which has a very short half-life, has generally been considered to be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 6 publications
5
21
1
Order By: Relevance
“…Yamasaki et al suggested that high levels of vascular endothelial growth factor (VEGF) expression are significantly related to the recurrence of meningioma, and that VEGF secretion from microscopic residue remaining after surgery may induce neovascularization, which promotes the recurrence of meningioma [55]. As to p53 immunohistochemistry, we found a close relationship among p53 immunoreactivity, MIB-1 SI, and recurrence [33]. Karamitopoulou et al found that a good correlation exists between histological grading, MIB-1 and p53 protein expression in meningiomas [26].…”
Section: ) Controversies Of Mib-1 Sisupporting
confidence: 56%
“…Yamasaki et al suggested that high levels of vascular endothelial growth factor (VEGF) expression are significantly related to the recurrence of meningioma, and that VEGF secretion from microscopic residue remaining after surgery may induce neovascularization, which promotes the recurrence of meningioma [55]. As to p53 immunohistochemistry, we found a close relationship among p53 immunoreactivity, MIB-1 SI, and recurrence [33]. Karamitopoulou et al found that a good correlation exists between histological grading, MIB-1 and p53 protein expression in meningiomas [26].…”
Section: ) Controversies Of Mib-1 Sisupporting
confidence: 56%
“…The cases that were immunoreactive tended to be strongly reactive, but only in a few nuclei. The overall proliferation index was unrelated to prognosis and therefore does not seem valuable in the workup of ear and temporal bone meningiomas (67)(68)(69).…”
Section: Discussionmentioning
confidence: 96%
“…The role of p53 has already been examined in the meningiomas: some of the examinations ended with negative or equivocal findings [43,[48][49][50], but some of them showed a significant correlation between the p53 status and the grade or recurrence of the tumour [4,7,8,19,20,28,37,41,44,46,57]. It is also described that p53 immunopositive cells are more frequent in the perinecrotic areas of post-embolised cases than in preserved parts of the tumour [39].…”
Section: Introductionmentioning
confidence: 99%